Biotoxicity assessment and lignocellulosic structural changes of phosphoric acid pre-treated young coconut husk hydrolysate for biohydrogen production. (1st March 2019) - Arisht, Shalini Narayanan; Abdul, Peer Mohamed; Liu, Chun-Min; Lin, Sheng-Kai; Maaroff, Rizal Muzhafar; Wu, Shu-Yii; Jahim, Jamaliah Md
Abstract: Major sugar constituents in young coconut husk were found to be glucans (0.30 g/g husk), while xylans were 0.10 g/g husk. Pre-treatments were carried out using phosphoric acid with dried coconut husk powder under steam heating. The effect of phosphoric acid on coconut husk hydrolysis was observed using acid concentrations of 0%, 1%, 5% and 10% (v/v). Soluble sugar concentration in hydrolysate was increasing proportional to acid concentration, as the total recovered solid decreases. FTIR and XRD analysis showed that acid hydrolysis led to the disruption of internal chemical bonds, causing coconut husk structural sugars to be released into the hydrolysate. Highest soluble sugar concentration, 29.9 g/L with a total suspended solid of 75.1 g/L, was obtained when the coconut husk was pre-treated with 10% phosphoric acid, and can be utilised for biohydrogen fermentation. Biotoxicity testing of the hydrolysates shows that half-maximal inhibition concentration of phosphoric acid was around 4.41% for a 24-h incubation and 3.80% for a 96-h incubation. Graphical abstract: Image 1 Highlights: Coconut husk sugar yield increases 18.3 g/L for 0% H3 PO4 to 29.9 g/L for 10% H3 PO4 . Biohydrogen yield of 0.68 mol H2 /mol sugar is obtained with 1% H3 PO4 hydrolysate. The half-maximal inhibition concentration of H3 PO4 is 4.41% for 24-h incubation. The decrease order of biotoxicity is 10% H3 PO4 > 5% H3 PO4 > 1% H3 PO4 > 0% H3 PO4 .